(untitled) (International journal of artificial intelligence, 2025)
in this article, Abdurauf fitrat's “the poet” was taken to the analysis of poetry. The essence of the poem , the reason to write, is to think about badiiyat. Also in the poem the poet of fitrat also nazariyotchi qualitydapplications of the approach through examples of revealed.